The Influence of Promotion on Purchasing Decisions of Zalora Marketplace Users - Nailin Nikmatul Maulidiyah (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study aims to analyze the effect of promotion on purchasing decisions of users in the Zalora marketplace in Jember. The research employs a quantitative approach using an explanatory research method. The data used are primary data collected through questionnaires distributed to Zalora users who have made at least one purchase, applying a purposive sampling technique. The research instrument utilized a Likert scale and was tested for validity and reliability. The data were analyzed using simple linear regression to examine the effect of the promotion variable on purchasing decisions. The results indicate that promotion has a positive and significant effect on purchasing decisions, as evidenced by a positive regression coefficient and a significance value of less than 0.05. These findings suggest that the more attractive and intensive the promotional programs—such as discounts, vouchers, and cashback the higher the likelihood that consumers will make purchasing decisions. This study implies that effective and sustainable promotional strategies are essential to enhance purchasing decisions and strengthen marketplace competitiveness.